Detection of Sarcocystis parasites in environmental samples from Lithuanian farms - Agnė Baranauskaitė; Petras Prakas; Modestas Petrauskas; Selene Rubiola; Elena Servienė; Živilė Strazdaitė-Žielienė (Food and Waterborne Parasitology)
Most studies on apicomplexan Sarcocystis spp. in domestic animals have primarily focused on examining animal carcasses using both morphological and molecular methods. However, to accurately assess the risk of Sarcocystis infections in livestock and to develop effective prevention strategies, it is essential to investigate the environmental reservoirs of these parasites. The aim of this study was to identify Sarcocystis species with domestic animals as intermediate hosts by analysing environmental samples (water, hay, and soil) collected from Lithuanian farms and to compare their occurrence across different sample types. In total, 90 environmental samples were collected over 3 years and analysed for the presence of Sarcocystis spp. using nested polymerase chain reactions targeting the cox1 gene. The results indicated that livestock are most likely to acquire infections via the ingestion of contaminated water or feed, while soil posed a lower risk of transmission. An assessment of species distribution across sampled farms revealed that the type of livestock raised did not influence the diversity of Sarcocystis spp. Notably, at least six of seven target species (S. arieticanis, S. bertrami, S. bovifelis, S. capracanis, S. cruzi, S. miescheriana, S. tenella) were detected at least once on eight of 10 farms. Additionally, two zoonotic Sarcocystis species, S. hominis and S. suihominis, were identified in environmental samples. This study emphasises the potential risk of livestock infection through contaminated environmental and feed sources and highlights the critical role of environmental monitoring in preventing the transmission of Sarcocystis spp. to farm animals.